A construção das personagens em Noite, de Érico Veríssimo e Um Rosto noturno, de Reynaldo Moura - Pieri, Jaqueline de Cássia Luz (2013)
Within the literary panorama of the state of Rio Grande do Sul, the novels Noite (1954) by Erico Verissimo, and Um rosto noturno (1946) by Reynaldo Moura give preference to what is fundamentally human and highlight the essence of the end, the destiny of men. The characters created by the writers, representing men, concern the human being in the universe, problematic, considered in their relations with others, society, history, and the transcendent. The texts by these writers are featured by reflexivity, that is, by the capacity of lead characters to direct their thoughts upon themselves. This work analyses the process of character construction, mostly lead characters, in the referred works, thus identifying the traits selected for the composition of fictional characters, and verifying the relation between character construction and the process of identity construction. It also aims to establish a parallel between the traits that constitute the characters by Verissimo in Noite and the features that make the fictional characters by Moura in Um rosto noturno